Triple cross how Bin Laden's master spy penetrated the CIA, the Green Berets, and the FBI--and why Patrick Fitzgerald failed to stop him - Lance, Peter (Regan, 2006)
In the years leading to the 9/11 attacks, no single agent of al Qaeda was more successful in compromising the U.S. intelligence community than Ali Mohamed. A former Egyptian army captain, Mohamed succeeded in infiltrating the CIA in Europe, the Green Berets at Fort Bragg, and the FBI in California?even as he helped to orchestrate the al Qaeda campaign of terror that culminated in 9/11. As investigative reporter Peter Lance demonstrates in this gripping narrative, senior U.S. law enforcement officials?including the now-celebrated U.S. attorney Patrick Fitzgerald, who personally interviewed Mohamed long before he was brought to ground?were powerless to stop him. In the annals of espionage, few men have moved between the hunters and the hunted with as much audacity as Ali Mohamed. For almost two decades, the former Egyptian army commando succeeded in living a double life. Brazenly slipping past watch lists, he moved in and out of the U.S. with impunity, marrying an American woman, becoming a naturalized citizen, and posing as an FBI informant?all while acting as chief of security for Osama bin Laden and Ayman Al-Zawahiri. Known to his fellow terrorists as Ali Amiriki, or "Ali the American," Mohamed gained access to the most sensitive intelligence in the U.S. counterterrorism arsenal while brokering terror summits, planning bombing missions, and training jihadis in bomb building, assassination, the creation of sleeper cells, and other acts of espionage.Building on the investigation he first chronicled in his previous books, 1000 Years for Revenge and Cover Up, Lance uses Mohamed to trace the untold story of al Qaeda's rise in the 1980s and 1990s. Incredibly, Mohamed, who remains in custodial witness protection today, has never been sentenced for his crimes. He exists under a veil of secrecy?a living witness to how the U.S. intelligence community was outflanked for years by the terror network.